ETIKA PROFESI HAKIM DALAM ISLAM - Khusnul Khotimah (Fakultas Syariah UINFAS Bengkulu, 2015)
Professional Ethics of Judges in Islam.Judge is a position that is noble in the sightof Allah, but full of risks and challenges, because the risks are so great, the islamic scholars hasset the conditions that must be fulfilled in order to occupy the post of judge, and formulateparticular ethics as a references of the judges so that it do not disobey Allah in al-Qur'an andHadith. A judge must have ethical values that will support the profession and show the authorityof the law in the eyes of the public, to then be justified On God and society. Thus upholding thesupremacy and rule of law is not merely wishful thinking and rhetoric